2002
DOI: 10.1007/s00216-002-1371-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of two ligno-cellulosic substrates by 13C CP/MAS NMR, XPS, conventional pyrolysis and thermochemolysis

Abstract: Ligno-cellulosic substrates (LCSs) isolated from wheat straw and bran exhibit high complexing capacities and may have important applications for metal removal from industrial effluents. These two LCSs were examined in the present work by spectroscopic and pyrolytic methods (solid state cross polarization magic angle spinning (CP/MAS) (13)C NMR, XPS, conventional Curie pyrolysis (Cupy)/GC/MS, and TMAH thermochemolysis/GC/MS). This combined study highlighted the limitation of some of the above methods when appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
(38 reference statements)
2
28
0
Order By: Relevance
“…These data are in accordance with the presence of an intense band at 30 ppm in the 13 C NMR spectrum, which was attributed to non-substituted alkyl (e.g. lipids), with IR bands at 2920 and 2850 cm -1 , and with pyrolysis GC-MS studies [26]. Atomic O/C ratios deduced from elemental (0.58) and XPS analysis (0.41) are slightly different, possibly because of preferential arrangement of the oxidized groups inside the solid.…”
Section: Spectroscopic Characterizationsupporting
confidence: 86%
See 1 more Smart Citation
“…These data are in accordance with the presence of an intense band at 30 ppm in the 13 C NMR spectrum, which was attributed to non-substituted alkyl (e.g. lipids), with IR bands at 2920 and 2850 cm -1 , and with pyrolysis GC-MS studies [26]. Atomic O/C ratios deduced from elemental (0.58) and XPS analysis (0.41) are slightly different, possibly because of preferential arrangement of the oxidized groups inside the solid.…”
Section: Spectroscopic Characterizationsupporting
confidence: 86%
“…Q max1 exceeded Q max2 , which was somewhat surprising because lignin is rich in phenol groups and contains few carboxyl functions [31]. Carboxyl functions might also originate from the presence of fatty acids [26]. The relatively high value of logK -1 , compared with those found by other authors [6,18,32] for humic substances, is consistent with the presence of fatty acids.…”
Section: Conductimetric Titrationssupporting
confidence: 70%
“…The common approach used to quantify the relative contribution of different C types to SOM is to integrate and compare peak areas of different spectra regions without considering any non-proportional signal responses (e.g., Kögel-Knabner, 2002). It has been shown that this approach underestimates lignin vs. cellulose in ligno-cellulose isolated from wheat (Gauthier et al, 2002).…”
Section: Analytical Limitationsmentioning
confidence: 99%
“…Nowadays, it has no real application, which constitutes a serious handicap for the rentability of the industrial treatment of wheat bran. Previous characterizations had revealed that the structure of the lignocellulosic substrate is composed of lignin and cellulose as its major constituents and a non-negligible proportion of fatty acid (Gauthier et al 2002). Lignin and fatty acids bear functional groups such as alcohol, ketone, and carboxylic groups, which can be involved in complexation reactions with metallic cations.…”
Section: Introductionmentioning
confidence: 99%